Z problematyki przestępczości przedsiębiorstw w prawie karnym gospodarczym : uwagi o systemie sankcji w ustawie o odpowiedzialności podmiotów zbiorowych za czyny zabronione pod groźbą kary - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Globalization and the interpenetration of complex economic structures, as well as new trends in economic crime require the creation of legal instruments which constitute an effective obstacle against the activity of entities that are not traditional (in terms of criminal law) perpetrators. It is, after all, collective entities that more and more often become direct animators and beneficiaries of criminal activities. The article will analyze the system of sanctions provided for against collective entities under the Act on the Liability of Collective Entities for Acts Prohibited under Penalty. The deliberations will also take into account the solutions provided for by the government bill on the liability of collective entities for prohibited acts under penalty, which was submitted to the Sejm of the previous term on 11 January 2019.
Keywords: liability of collective entities; corporate crime; penal economic law; economic crimes